Thermus thermophilus Argonaute-based signal amplifier for highly sensitive and specific microRNA detection - Wang, Ziqi; Wang, Zitong; Zhang, Fan; Wu, Lingyi (Frontiers in Bioengineering and Biotechnology, 2023)
Prokaryote-derived gene defense system as a new generation of nucleic acid detection tool exhibits impressive performance in the field of molecular diagnosis. Prokaryotic Argonaute (Ago) is a CRISPR-associated protein that is guided by a short DNA (gDNA) and then efficiently cleave gDNA-complementary nucleic acids, and presents unique characteristics that are different from CRISPR/Cas system. However, the application of Ago in biosensing is still relatively few, and many properties of Ago need to be further clarified. In this study, we aim to systematically explore the properties of Thermus thermophilus Argonaute (TtAgo), including the dependence of TtAgo activity on guide DNA (gDNA) length, substrates’ length and the position of gDNA complementary region on substrate, etc. Based on these properties, we constructed an exonuclease III-assisted target-recycled amplification system (exoAgo) for sensitive miRNA detection. The result showed exoAgo can be used for miRNA profiling with a detection limit of 12.2 pM and single-base-resolution, and keep good performance for the detection of complex samples, which indicates Ago has a great application potential in nucleic acids detection. In conclusion, this study will provide a guidance for further development and utilization of Ago in the field of biosensing.